Education as a Da'wah Media: An Analysis of Ahmad Dahlan's Reform Movement - Feri Anugrah (Sahabat Publikasi, 2026)
This article examines the educational reform ideas and movements of Ahmad Dahlan as an integral part of his Islamic da'wah mission. The study focuses on how Ahmad Dahlan formulated a modern education system that integrated Islamic values with the Western education system in response to the educational dualism prevalent during the colonial period. A qualitative-descriptive approach was employed. The findings show that Ahmad Dahlan not only purified Islamic teachings from irrelevant practices but also carried out reforms by establishing a progressive Islamic education system—despite initial opposition from many. He founded Madrasah Ibtidaiyah Diniyah Islamiyah in 1911 and established Muhammadiyah in 1912 as a vehicle for education-based da'wah. His innovations included an integrated curriculum combining religious and general sciences, systematic classical methods, and instilling exemplary values in teachers. Thus, for Ahmad Dahlan, education served as a strategic means of da'wah to educate, liberate, and advance the ummah spiritually and socially.